Clinical And Ultrasonographic Evaluation Of Bitches Affected With Pyometra - Gupta, A.K.; Dhami, A.J.; Patil, D.B.; Kumar, Dharmendra; Darr , M. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Among the common major reproductive disorders in bitches, canine pyometra is a major one. Total nine bitches having gynaeco-clinical signs suspected of pyometra were evaluated by abdominal palpation and ultrasonography using 2.5-7.5 MHz sector probe through ventral midline approach. Ultrasonographic images of anechoic to hypoechoic fluid filled uterus with thick uterine wall confirmed all the nine bitches to be pyometric. The general condition of bitches with closed pyometra was poor, whereas it was fair in cases of open pyometra. The distension of abdomen was apparent in 33.33% cases and on palpation also the uterus was found distended. Inappetance, fever and vomition was observed in 88.89, 77.78 and 55.56 % of pyometric bitches, while toxaemia, polyuria and polydipsia were present in 77.78, 66.67 and 77.78 % of bitches, respectively. Vaginal discharge sticking to the hair of tail and perineum was present in all 6 cases of open pyometra and it’s colour varied from gray to chocolate with foul odour. Abdominal palpation was clear in 3 cases and unclear in 6 cases. It is thus concluded that ultrasonography is an effective diagnostic tool for the qualitative and quantitative evaluation and diagnosis of canine pyometra.
Keywords: Bitch; Clinical signs; Diagnosis; Pyometra; Ultrasonography